Chinese Herbal Medicine and Its Regulatory Effects on Tumor Related T Cells - Hoffman, Robert D.; Li, Chang-Yu; He, Kai; Wu, Xiaoxing; He, Bai-Cheng; He, Tong-Chuan; Gao, Jian-Li (Frontiers in Pharmacology, 2020)
Traditional Chinese medicine is an accepted and integral part of clinical cancer management alongside Western medicine in China. However, historically TCM physicians were unaware of the chemical constituents of their formulations, and the specific biological targets in the body. Through HPLC, flow cytometry, and other processes researchers now have a much clearer picture of how herbal medicine works in conjunction with the immune system in cancer therapy. Among them, the regulation of tumor-related T cells plays the most important role in modulating tumor immunity by traditional Chinese medicine. Encouraging results have been well-documented, including an increase in T cell production along with their associated cytokines, enhanced regulation of Tregs and important T cell ratios, the formation and function of Tregs in tumor microenvironments, and the promotion of the number and function of normal T Cells to reduce conventional cancer therapy side effects. Chinese herbal medicine represents a rich field of research from which to draw further inspiration for future studies. While promising agents have already been identified, the vast majority of Chinese herbal mechanisms remain undiscovered. In this review, we summarize the effects and mechanisms of specific Chinese herbs and herbal decoctions on tumor related T cells.